IDENTIFICATION OF WHITE NOISE AND 1/f IN CURRENT MIRROR CONFIGURATION BASED ON VDS MOSFET - Maria Rosariana Gea; Lazuardi Umar; Rahmondia Nanda Setiadi (JOURNAL ONLINE OF PHYSICS, 2022)
Identifying noise in the Current Mirror (CM) circuit is essential to locate noise signals in biosensor applications so that measurements become more accurate and precise. There are two dominant types of noise: white noise, which consists of thermal noise and shot noise, and also low-frequency noise (1/f  noise). The main component of the CM circuit is the BS250 type MOSFET, which works by varying the width of the charge carrier channelcontrolled by the voltage at the gate. When the drain is given a voltage, electrons will flow from the source to the drain which generates the noise.This study was carried out to identify the noise in the CM configuration by varying the reference voltage of MOSFET using the PCI-6221 card data integrated with the LabVIEW program. The reference voltage values ​​used are 1 mV, 10 mV, and 100 mV to determine the effect of the input voltage on the CM circuit noise signal, while the measurement frequency is varied from 0.1 Hz to 100 kHz with a resolution of 0.1 Hz. The results show that the noise characteristics vary with the applied voltage, which will increase at a higher voltage. Analysis of 1/f noise at frequencies up to 0.2 Hz has a gradient increase of up to 10 times for each given voltage value. Based on the value of the data distribution on the white noise measurement, it shows that a voltage of 100 mV produces the highest noise with an average of 3.62 × 10-7 Vrms/Hz1/2. The results of this study are used in the design of CM circuits with minimal noise.